Globalization and corporate taxation - Kumar, Manmohan S. (IMF working paper, 2012)
This paper analyzes the extent to which the degree of international economic integration, both financial and trade, affects corporate tax rates. It explores this issue in the context of strategic behavior by countries, taking into account other global and domestic political economy factors. Tax rates are analyzed using a unique tax dataset for advanced and developing economies extending over five decades. We report a number of novel results: there is no general negative relationship between financial globalization and corporate tax rates and revenues--results vary according to country grouping with OECD countries showing a positive relationship; the United States exhibits a "Stackelberg" type of leadership on other countries; trade integration is inversely correlated with tax rates; and public sentiment and ideology affect tax rates. The policy implications of these findings, particularly given budgetary pressures in the aftermath of the global crisis, are noted.